2014
DOI: 10.1002/2014eo340001
|View full text |Cite
|
Sign up to set email alerts
|

Cold Water and High Ice Cover on Great Lakes in Spring 2014

Abstract: Very cold temperatures across much of North America caused by the recent anomalous meridional upper air flow—commonly referred to in the public media as a polar vortex (for details, see Blackmon et al. [1977] and National Climatic Data Center, State of the climate: Synoptic discussion for January 2014, http://www.ncdc.noaa.gov/sotc/synoptic/2014/1)—have contributed to extreme hydrologic conditions on the Great Lakes. The Great Lakes are the largest system of lakes and the largest surface of freshwater on Earth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Sci. Discuss., https://doi.org /10.5194/hess-2017- comparison between two unusually warm (2012-2013) and unusually cold (2013-2014) winters (Clites et al, 2014).…”
Section: Methods 25mentioning
confidence: 99%
See 1 more Smart Citation
“…Sci. Discuss., https://doi.org /10.5194/hess-2017- comparison between two unusually warm (2012-2013) and unusually cold (2013-2014) winters (Clites et al, 2014).…”
Section: Methods 25mentioning
confidence: 99%
“…On the Laurentian Great Lakes (hereafter referred to as the Great Lakes), sensible and latent heat fluxes play an important role in the seasonal and interannual variability of critical physical processes including spring and fall lake evaporation (Spence et al, 2013), the onset, retreat, and 15 spatial extent of winter ice cover (Van Cleave et al, 2014;Clites et al, 2014), and air-mass modification including processes such as lake-effect snow (Wright et al, 2013). These phenomena, in turn, impact lake water levels (Gronewold et al, 2013;Lenters, 2001), both atmospheric and lake circulation patterns (Beletsky et al, 2006), and the fate and transport of watershed-borne pollutants (Michalak et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The Great Lakes' rapid warming may be viewed as an abrupt LST increase from 1997 to 1998 in response to the strong 1997–1998 El Niño episode (Assel ; Clites et al ), followed by a sustained elevation of the LSTs (Gronewold et al ), or alternatively, in response to the shift of the Pacific Decadal Oscillation (PDO) toward its negative phase (Van Cleave et al ). The abrupt change from 1997 to 1998 (Fig.…”
Section: Decadal Regime Shift and Abrupt 1997/1998 Changementioning
confidence: 99%
“…In a study by Austin and Colman [], surface water temperature in Lake Superior was reported to be increasing at a faster rate (0.12°C/yr) than the surrounding air temperature through a positive feedback involving lake temperature, absorption of the surface heat flux and ice coverage [ Austin and Colman , ]. In addition, large climate variability such as extremely cold water and high ice coverage on the Great Lakes has been frequently observed [ Wang et al ., ; Clites et al ., ]. Strong “thermal inertia” is considered one of the major reasons for the important leads and lags between water temperature, evaporation and ice coverage in the coupled lake‐atmosphere system [ Spence et al ., ; Lenters et al ., ].…”
Section: Introductionmentioning
confidence: 99%